ANALISIS MAKNA LAGU “LIHAT, DENGAR, RASAKAN” DARI SHEILA ON 7 MENGGUNAKAN PENDEKATAN SEMIOTIKA - Asep Tian Dwi Cahya; Riana Dwi Lestari; Ika Mustika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2021)
Song is part of the music in the form of the text that is sung. Song lyrics are also an inspiration that comes from thoughts and feelings accompanied by tones and rhythms. There is a meaning or message that musicians convey through the lyrics of the songs they make. Likewise with the song lyrics See, Listen, Feel from Sheila On 7. Therefore, this research was conducted to find out the meaning contained in this song by using a descriptive method which was carried out by describing each of the lyrics, then studied using a semiotic approach so that You can interpret it by giving a signifier and signified so that the meaning in this song can be known. This research was conducted in several steps, namely: (1) choosing a song, (2) analyzing the song by dividing the lyrics into several verses, (3) analyzing the verse with Saussure's semiotic theory, (4) determining the signifier and signified ), and (5) describe the results. The results of this study which became the signifier were the lyrics of the song "See, hear, feel" and the sign (signified) was the result of the meaning of the lyrics.